Research Gaps and Recommendations to Guide Research on Assessment, Prevention, and Treatment of Moral Injury Among Healthcare Workers - Maguen, Shira; Griffin, Brandon J. (Frontiers in Psychiatry, 2022)
Healthcare workers face numerous occupational stressors, including some that may challenge personal and shared morals and values. This is particularly true during disasters and crises such as the COVID-19 pandemic, which require critical decisions to be made with little time and information often under personal distress and situational constraints. Consequently, healthcare workers are at risk for moral injuries characterized by stress-related and functional impacts. Although evaluation and treatment of moral injury among military veterans burgeoned in the recent decade, addressing moral injury in healthcare workers and other civilians remains an important gap. In this perspective piece, we identify research gaps and make recommendations to advance future work on assessment, prevention, and treatment of moral injury in healthcare workers. We draw on empirical studies of moral injury in veterans, limited studies of moral injury in health professionals, and our clinical experiences with healthcare workers affected by moral injury.